Manajemen Pelatihan Desain Grafis di Lembaga Pendidikan Dan Pengembangan Profesi Bina Profesional Mandiri (LP3-BPM) Kota Tasikmalaya - Rahma, Ima Sofia; Herwina, Wiwin; Hamdan, Ahmad; Sumiarsih, Mia (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2023)
The purpose of this study is to describe training management applied to graphic design training in LP3-BPM Tasikmalaya City. This research uses a descriptive research method with a qualitative approach that aims to provide a natural picture of the symptoms and conditions that occur. The data sources used are primary and secondary data obtained from 4 informants as well as institutional administrative data. The result of this study is that graphic design training management at LP3-BPM Tasikmalaya City is carried out with the Training Needs Analysis (AKP) stage, determining training objectives, curriculum development, training planning, training implementation and training evaluation